Effect of Y0.5Gd0.5TaO4 additions on the microstructures, mechanical properties and thermophysical properties of NbMoTaW refractory high-entropy alloy. (February 2023) - Zhang, Zhibin; Wan, Yixing; Sun, Bo; Zhang, Shuyan; Chong, Xiaoyu; Feng, Jing; Liang, Xiubing
Abstract: Combining the advantage of the refractory high-entropy alloys (RHEAs) and rare-earth tantalate, the effect of Y0.5 Gd0.5 TaO4 on the microstructures, mechanical properties and thermophysical properties of NbMoTaW was studied. The microstructures were stable after addition of the rare-earth tantalate. With increasing Y0.5 Gd0.5 TaO4 contents, the hardness increased gradually, while the compressive strength and fracture strain decreased. The addition of Y0.5 Gd0.5 TaO4 was effective in increasing the thermal diffusivity, but had little effect on the linear thermal expansivity. This study fills the vacancy of the effect of rare-earth tantalate on the microstructures, mechanical properties and thermophysical properties of RHEAs and provides guidance for the design of RHEAs. Highlights: NbMoTaW- x (Y0.5 Gd0.5 TaO4 ) RHEAs with good thermophysical properties were designed. The effect of Y0.5 Gd0.5 TaO4 on the microstructures and properties was studied. The addition of Y0.5 Gd0.5 TaO4 is effective in increasing of thermal diffusivity.